Current Situation of Medication Adherence in Hypertension - Vrijens, Bernard; Antoniou, Sotiris; Burnier, Michel; de la Sierra, Alejandro; Volpe, Massimo (Frontiers in Pharmacology, 2017)
Despite increased awareness, poor adherence to treatments for chronic diseases remains a global problem. Adherence issues are common in patients taking antihypertensive therapy and associated with increased risks of coronary and cerebrovascular events. Whilst there has been a gradual trend towards improved control of hypertension, the number of patients with blood pressure values above goal has remained constant. This has both personal and economic consequences. Medication adherence is a multifaceted issue and consists of three components: initiation, implementation and persistence. A combination of methods is recommended to measure adherence, with electronic monitoring and drug measurement being the most accurate. Pill burden, resulting from free combinations of blood pressure lowering treatments, makes the daily routine of medication taking complex, which can be a barrier to optimal adherence. Single-pill fixed-dose combinations simplify the habit of medication taking and improve medication adherence. Re-packing of medication is also being utilized as a method of improving adherence. This paper presents the outcomes of discussions by a European group of experts on the current situation of medication adherence in hypertension.